Qualidade de vida e satisfação no trabalho: percepções das pessoas com deficiência inclusas no mercado de trabalho - Lopes, Sergio Martins (2013)
The quality of life at work has been studied from different theoretical and methodological approaches, but always focused on understanding ways to bring satisfaction and well-being at worker. This study aimed to evaluate the quality of life and job satisfaction of people with disabilities included in employment programs. We sought to analyze the relationships between the dimensions of job satisfaction and quality of life domains. Adopting a quantitative approach, was used two questionnaires: Quality of Life Index (QLI) by Ferrans and Powers and Job SatisfactionQuestionnaireS20/23byMeliáandPeiro. 15 individuals with physical disabilities were assessed. The results showed that the average total quality of life index of the participants was 18.06(SD = 1.88), with scores ranging between13.30and21.26, the rating for the quality levels of the group presented a good quality. The mean total questionnaireS20/23 participants was 4.03(SD = 0.86), with scores ranging between 2.30 and 5.00 for job satisfaction, compared with the scale to the levels of satisfaction, the group showed a partial job satisfaction. When comparing the total score of the QLI and its domains with the total score of the questionnaire and its dimensions S20/23 results showed no correlations between its components. It is believed that these findings may stimulate research involving this issue and the results used as the basis for the development of a culture of improving the quality of life and job satisfaction of people with disabilities.